PENGARUH KEPUASAN KERJA DAN LINGKUNGAN KERJA NON FISIK TERHADAP DISIPLIN KERJA SERTA DAMPAKNYA TERHADAP KOMITMEN PT.ISOPLAN - Kusuma, Moch Aditya Hadi; Kustini, Kustini (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
The purpose of this study is to prove the effect of the relationship between job satisfaction and non-physical work environment on discipline and its impact on commitment. The population of this study were employees and the sample used was 52 respondents. The sampling method used a saturated sample technique. The data used are primary data, while the data analysis used in this study is Partial Least Square (PLS). Based on the results of the study, it can be seen that job satisfaction has a contribution to organizational commitment, which means that the better job satisfaction is carried out, the better the results of organizational commitment obtained. The non-physical work environment has a contribution to organizational commitment, which means that the better the non-physical work environment, the better the results of organizational commitment obtained. And Work Discipline has a contribution to employee performance, which means that the better the work discipline in a company, the higher the employee performance results.